1996
DOI: 10.1172/jci118737
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-associated point mutations in the adducin alpha and beta subunits affect actin cytoskeleton and ion transport.

Abstract: The adducin heterodimer is a protein affecting the assembly of the actin-based cytoskeleton. Point mutations in rat adducin ␣ ( F316Y ) and ␤ ( Q529R ) subunits are involved in a form of rat primary hypertension (MHS) associated with faster kidney tubular ion transport. A role for adducin in human primary hypertension has also been suggested. By studying the interaction of actin with purified normal and mutated adducin in a cell-free system and the actin assembly in rat kidney epithelial cells (NRK-52E) transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
196
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(208 citation statements)
references
References 47 publications
9
196
0
3
Order By: Relevance
“…Early transfection studies with the mutant rat α-adducin (316Y) into renal cells revealed a rearrangement of the cytoskeleton (potentially by an accelerated actin polymerization) associated with an increased Na + /K + ATPase activity (Tripodi et al 1996). More recently, expression of rat and human α-adducin variants has been implicated in a reduced endocytosis of Na + /K + ATPase molecules (Efendiev et al 2004).…”
Section: Polymorphisms In Adducin Genesmentioning
confidence: 99%
“…Early transfection studies with the mutant rat α-adducin (316Y) into renal cells revealed a rearrangement of the cytoskeleton (potentially by an accelerated actin polymerization) associated with an increased Na + /K + ATPase activity (Tripodi et al 1996). More recently, expression of rat and human α-adducin variants has been implicated in a reduced endocytosis of Na + /K + ATPase molecules (Efendiev et al 2004).…”
Section: Polymorphisms In Adducin Genesmentioning
confidence: 99%
“…7,12,[26][27][28][29][30][31][32] The overall evidence from these experimental and clinical studies indicates that Trp allele carriers have an increased risk of hypertension attributable to an innate stimulation of the sodium pump and enhanced renal tubular sodium reabsorption. 7,[33][34][35][36][37] However, most studies in humans suggest that mutation of the a-adducin gene on its own is insufficient to cause hypertension. 12 Indeed, the pathogenesis of high BP is complex, involves multiple genes, and lifestyle and environmental factors.…”
Section: Br Davis Et Almentioning
confidence: 99%
“…9 Transfection studies with cDNA from the MHS showed altered ability of adducin to interact with actin and increased maximum velocity of the sodium-potassium pump. 18 In humans, polymorphic markers flanking the ␣-adducin gene have been shown to be associated with primary hypertension in Italians 19 and linkage has been demonstrated between the ␣-adducin locus and primary hypertension in French families. 20 The tryptophane variant of a polymorphism in the ␣-adducin gene which codes for either glycine or tryptophane at codon 460 (Gly460Trp) has been associated with hypertension in Italian, French and Japanese populations.…”
Section: Introductionmentioning
confidence: 99%